Correlates Of Recidivism Among Released Prisoners: A Study of Kakamega County, Kenya - Luyt, Willem FM (2021)
Released prisoners in Kenya have a 75% likelihood of committing another crime and a 50% probability of going to jail two years after their discharge from prison custody. From the trend of recidivism in Kenya, there are a staggeringly high number of offenders being incarcerated and eventually released back to the community, and the high risk of re-arrest and re-incarceration is a concern for policymakers, criminologists and correctional managers. This study examined the influence of offender characteristics, offender reintegration and community perception and attitude regarding recidivism in Kakamega County, Kenya. The study adopted a survey research design. Findings reveal a statistically significant relationship between offender characteristics and recidivism. In addition, offender reintegration and community perception and attitude towards offenders greatly influence recidivism. From the study, it is recommended that the government provide correctional officers with the required resources to use the actuarial risk assessment model. The model is applied to the released offenders to predict the future probability of recidivism. In addition, it is recommended that the government and the various correctional stakeholders come up with an integrated approach that specifically targets successful re-entry of offenders upon release from prison. Finally, it is recommended that the government develop programmes targeting awareness of the community members to desist from stigmatising ex-offenders. Key terms: Correlates, Recidivism, Prisoners, Kenya DOI: 10.7176/JLPG/109-07 Publication date:May 31st 202